NEW TECHNIQUES IN CONSOLIDATIONS. - Newlove, G. H. (The Accounting Review, 1953)
Abstract The article discusses modifications made to a family tree introduced by scholar Lewis A. Carman in 1932. He used the tree to analyze the use of equity ratios in distributing the combined capital stock and surplus on the balance sheets of companies affiliated by both unilateral and bilateral common stockholdings. The family tree is adapted very slightly to have it obey some modem principles of family tree construction like arrows point with the force of authority, percentages of ownership and separate family trees are made for each class of stock. In 1948, the use of equity ratios was extended to the preparation of income and surplus statements involving both common and preferred stockholdings, and a mechanical method of calculating the equity ratios was introduced for use after the ratios of the bilateral groups have been computed. In 1949, a new formula for computing the equity ratios for bilateral stockholdings was developed in an advanced course in consolidations at The University of Texas by Myles Joseph Aaronson. The new formula is very simple to use because the determinant aspects cancel out leaving an equation, which enables anyone to handle the most difficult cases of mutual stockholdings, by using only simple arithmetic processes.